2014
DOI: 10.1007/s10404-014-1533-5
|View full text |Cite
|
Sign up to set email alerts
|

Model of droplet generation in flow focusing generators operating in the squeezing regime

Abstract: considers the influences of channel geometry (height-towidth ratio), viscosity contrast, flow rate ratio and capillary number with a wide variety. This model is validated by comparing predictions from the model with experimental results obtained through high-speed imaging. List of symbolsChannel height L eqv Equivalent droplet length of the uniform cross section L fill Droplet length that penetrates into the main channel at the end of the filling stage L gutter Length of the gutter at the end of the necking st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…In lithographically fabricated poly(dimethylsiloxane) (PDMS) devices, there are various channel geometries that can be applied to the droplet breakup, including T‐junction , co‐flow , and flow‐focusing , as shown in Fig. 2A.…”
Section: Droplet‐based Microreactormentioning
confidence: 99%
“…In lithographically fabricated poly(dimethylsiloxane) (PDMS) devices, there are various channel geometries that can be applied to the droplet breakup, including T‐junction , co‐flow , and flow‐focusing , as shown in Fig. 2A.…”
Section: Droplet‐based Microreactormentioning
confidence: 99%
“…The total flow rate is kept constant in the experiments (5 µL/min) to ensure the residence time of the droplet in the channel is the same. However, the length of the droplets is known to be influenced by the material properties of the fluid phases (Utada et al 2007;Chen et al 2014), and in the experiment this effect is partly adjusted for by changing the water:oil flow ratio. For generation of water droplets in olive oil, the flow ratio is set to 2:3 compared with 1:4 for generation of water droplets in fluorinated oil.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…There have been numerous studies reported on droplet micro-uidics over the past decade as summarized by a number of review articles. [1][2][3][4][5] Fundamental studies mainly focus on investigating and elucidating two phase ow and transport phenomena as well as exploring functionalities for droplet manipulation, [6][7][8][9][10][11][12] while application driven studies aim to exploit droplet microuidics to address the challenges associated with the current best practices. [13][14][15][16][17][18] Both active and passive methods have been developed for manipulating droplets such as droplet generation, merging, splitting and trapping.…”
Section: Introductionmentioning
confidence: 99%